Formulation and Characterization of Poly(methyl methacrylate) Microcapsules Encapsulating Peppermint and Origanum Essential Oils - Dr. Manoj Shetty, (Asian Journal of Pharmaceutics (AJP), 2025)
Introduction: Peppermint and origanum essential oils are known for their strong antimicrobial, antifungal, and antibiofilm properties. Despite their effectiveness, their clinical use is limited due to high volatility, poor water solubility, and instability under environmental conditions. Microencapsulation using biocompatible polymers like poly(methyl methacrylate) (PMMA) can help overcome these limitations by improving stability and enabling controlled release. Materials and Methods: Microcapsules were prepared using a modified solvent evaporation method. A mixture of peppermint and origanum oils in a 100:75 ratio was combined with PMMA in dichloromethane. This organic phase was emulsified into an aqueous phase containing 1% polyvinyl alcohol and 2 g sodium lauryl sulfate. The mixture was stirred for solvent evaporation, followed by centrifugation to isolate the microcapsules. The capsules were then analyzed for ultraviolet (UV) absorbance, particle size, morphology, yield, and entrapment efficiency (EE). Results: UV-visible spectrophotometry showed λmax at 253 nm for peppermint oil and 276 nm for origanum oil. BIOVIS microscopy revealed that 99.24% of the capsules were in the 0.5–5 µm range. SEM images showed spherical particles with smooth surfaces and no cracks. The yield was 70%, with 1050 mg recovered from 1500 mg. EE ranged from 33.39% to 50.64%, with 37.83–45.00% for peppermint oil and 27.58–58.00% for origanum oil. Discussion: The PMMA microencapsulation method effectively produced uniform and stable microcapsules. The particle size and surface morphology support their potential for controlled delivery. Moderate entrapment efficiencies suggest room for optimization, possibly influenced by differences in the physicochemical properties of the oils. Overall, the method showed promise in enhancing oil stability and reducing volatility. Conclusion: PMMA-based microencapsulation successfully stabilized peppermint and origanum oils, offering good yield, structure, and encapsulation efficiency. This system holds potential for future applications in controlled-release formulations for antimicrobial therapies.